Studying asphalt binder fatigue pattern by using a dynamic shear rheometer (2011)
This article was aimed at determining fatigue test results regarding different types of binder when using a dynamic shear rheometer (DSR). The tests were carried out in stress conditions at 20ºC. The stress input signal was a constant amplitude, 1.59 Hz frequency sine wave. Asphalt binders B-13/22, B-40/50, B-60/70, B-80/00, B-150/200 and BM-3c (modified asphalt) were studied. The test measured strain, complex modulus (G*), dissipated energy and dissipated energy ratio (DER) with the number of cycles. Strain criteria were used for determining binder fatigue failure (DER). Failure was defined as the point at which (DER) dropped 10% after peaking. Laws of asphalt fatigue were obtained from the strain and failure cycle results.